Analisis Aktivitas Hambatan Samping Terhadap Arus Lalu Lintas di Jalan Batu Cermin, Kota Labuan Bajo - Petrus Yudosensius Pedro Bagut; Andi Kristafi Arifianto; Blima Oktaviastuti (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
Roads are an essential form of land transportation that promotes access to everyday essentials, community movement, and economic activity. The purpose of this research is to determine the presence of side barriers on Labuan Bajo City's Batu Cermin Street, examine them, and assess how they affect traffic flow. The data gathered using a quantitative descriptive research technique included autos entering and exiting side accesses, slow-moving vehicles, parked or stopped cars, and pedestrians. According to the research, side barriers were rather common, with values of 3,469.4 in the south and 3,054.3 in the north. The primary sources of these issues include haphazard parking practices, roadside street sellers, and traffic movement from side lanes to the main road. Road performance is severely disrupted by these circumstances, which also delay traffic and raise the possibility of congestion. The results of the research lend credence to the idea that side barriers should be taken into account when organizing and overseeing urban transportation, as they are an essential part of traffic flow. Therefore, to improve traffic conditions in this region, improved management measures are required, including the provision of sufficient parking spaces and the arranging of street sellers.